Examining barriers and facilitators to implementing evidence-based genetic risk-stratified breast cancer screening in primary care - Guan, Yue; Barge, Haley; Escoffery, Cam; Cellai, Michele; Alfonso, Susana; Johnson, Theodore M. (Frontiers in Cancer Control and Society, 2025)
IntroductionWhile there is strong evidence supporting family cancer history screening as a tool for risk-stratified cancer screening, challenges in implementation remain. Many efforts tend to focus solely on the high-risk pathway neglecting the entire patient population. This study aims to capture primary care providers' perspectives on implementing genetic-informed, risk-stratified mammography screening guidelines.MethodsSemistructured interviews were conducted involving 14 providers and 5 practice leaders across 2 Georgia healthcare systems between November 2020 and May 2021. Interviews assessed the barriers and facilitators at patient, provider, and system levels using the Consolidated Framework for Implementation Research. Thematic analysis was conducted using MAXQDA, and Fishbone analysis was applied to summarize the results.ResultsBarriers and facilitators differed between high- and low-risk pathways. For high-risk pathways, barriers included limited provider knowledge and unclear referral protocols, while facilitators included established relationships between providers and genetic professionals and effective electronic health record systems. For low-risk pathways, barriers centered on provider acceptance, guideline inconsistency, and risk communication challenges.ConclusionEffective implementation of risk-stratified breast cancer screening requires tailored strategies to address pathway-specific barriers. Integrating ongoing education, clinical decision support, and workflow alignment may enhance program adoption.